Auditory Spatial Illusion – A Psychoacoustic Study in Young Adults - MALEKI, Mehri; AHADI, Mohsen; JAFARPISHEH, Amirsalar; ASGHARZADEH, Amin; BAGHBAN, Alireza Akbarzadeh; TOUFAN, Reyhane (Archives of Acoustics, 2024)
The Franssen illusion, or Franssen effect (FE), is one of the auditory spatial illusions. Few studies have explored the FE, and the mechanisms underlying it remain unknown. The present study was conducted to clarify the FE occurrence with different tasks and presentation modes in young adults. It also sought to investigate possible neurophysiological similarities between interaural time difference (ITD) cue processing and FE perception. FE perception was evaluated using two different tasks and two presentation modes (i.e., insert phones and loudspeakers). Sound reflections (reverberation) were presented in the diffuse field (loudspeaker mode). ITD performance was investigated using different stimuli delivered via insert phones. No significant difference between the two FE perception tasks was found (F1;25 = 0:138, p = 0:713). However, the FE perception showed a significant difference between the two presentation modes (F1;25 = 434:03, p < 0:001). Spearman’s correlation did not reveal a significant relationship between FE perception and ITD scores (p > 0:05). The current findings show the importance of reverberation in the FE occurrence. Also, the non-significant correlation between the results of the behavioral binaural temporal resolution test and FE perception in young people with normal temporal resolution may indicate that room reflections (reverberation) complicate the ability to process ITDs (rather than poor ITD processing for the “steady state” portion of signal).